1970
DOI: 10.22270/ajprd.v7i6.619
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Moringa Seed Oil Nanoemulsion Gel

Abstract: Objective: The objective of this study was to formulate and evaluate the moringa seed oil (MSO) nanoemulsion gel using high-energy emulsification method. Methods: Nanoemulsion gel formulated by high-energy emulsification method using the comparison of surfactant (tween 80) and cosurfactant (sorbitol) concentration with the variation of moringa seed oil concentration. Evaluation of the stability of the nanoemulsion gel preparation includes centrifugation test, viscosity, pH, organoleptic observation (odor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…TEM results of the prepared NEs showed sufficient degradation ability which was consistent with DLS test results. These results were almost similar to ( Justina and Syurya, 2018;Tirmiara et al, 2019) who found that loaded Eos of the NEs had a spherical form and were mono or dispersed with a regular distribution. In addition, the shape and size of NEs allowed them to penetrate the bacterial cell wall and increasing the antibacterial inhibition (Athikomkulchai et al, 2021).…”
Section: Figure 1: Difference Between Mo and Its Nan-emulsionsupporting
confidence: 90%
See 1 more Smart Citation
“…TEM results of the prepared NEs showed sufficient degradation ability which was consistent with DLS test results. These results were almost similar to ( Justina and Syurya, 2018;Tirmiara et al, 2019) who found that loaded Eos of the NEs had a spherical form and were mono or dispersed with a regular distribution. In addition, the shape and size of NEs allowed them to penetrate the bacterial cell wall and increasing the antibacterial inhibition (Athikomkulchai et al, 2021).…”
Section: Figure 1: Difference Between Mo and Its Nan-emulsionsupporting
confidence: 90%
“…To detect how much EO and surfactants are needed to make the most stable NE in an O/W nano-emulsion of one oil at room temperature varied according to the viscosity of the oil. According to (Tirmiara et al, 2019) the Nano-MO was produced but instead of DMSO, Tween*80 and MO were added in a 1:3 (v/v) ratio, and the mixture was then centrifuged at 500 rpm for ten minutes using a magnetic stirrer. Then it was sonicated at 750W for five minutes at 20 kHz in a USH650 ultrasonicator with a 750 watt max output then filter the NEs at 0.22 m (200 nm), (Elsherif and Al Shrief, 2021).…”
Section: Nano-emulsion (Ne) Preparationmentioning
confidence: 99%
“…This study demonstrated a new cream/emulsion formulation containing M. oleifera seed oil as the active ingredient. The 25% of moringa seed oil was found to be the high concentration of moringa seed oil incorporated into the cream/emulsion formulation [32,33]. The high concentration of moringa seed oil could result in an unstable emulsion.…”
Section: Discussionmentioning
confidence: 98%
“…Viscosity measurement was investigated by a viscometer, the emulsion was transferred on pot film and measured using spindle number 4 (Tirmiara et al, 2019).…”
Section: Viscosity Testmentioning
confidence: 99%